An Analysis of Precipitation Extremes in the Inner Mongolian Plateau: Spatial-Temporal Patterns, Causes, and Implications - Chunlan Li and Walter Leal Filho and Jun Wang and Hobert Fudjumdjum and Mariia Fedoruk and Richa Hu and Shan Yin and Yuhai Bao and Shan Yu and Julian David Hunt (Atmosphere, 2018)
To improve how extreme events and climate variations are managed, there is a need to foster a deeper understanding of their interconnections. Consistent with this objective, this paper describes how precipitation extremes change both temporally and spatially in the Inner Mongolian Plateau (IMP), China and explains their causal factors. The paper refers to data collected from 43 meteorological stations in IMP and describes how precipitation extremes formed and how they influence agriculture. Data gathered and presented in this paper may be useful in understanding the extent to which the IMP is being influenced by global environmental change. This study reveals that the eleven precipitation extremes indices, except the number of precipitation days with over 0.5 mm (R0.5), number of heavy precipitation days (R10), and total precipitation in wet days (PRCPTOT), decreased in the IMP between 1959 and 2014, and most of them were non-significant in temporal. But the dry index has a larger magnitude decreasing trend than that of the wet indices, which can indicate that the dry situation was alleviated in IMP during the study interval. This study also indicated that precipitation extremes have strong relationships with elevation, latitude, and longitude. Atmospheric circulation and topography may be further primary reasons which result in the spatial variation characteristics in precipitation extremes over the IMP. Decreases in precipitation extremes, together with human activities such as livestock improvement and ecological restoration programs, has a positive effect in gross output value of agriculture and animal husbandry in the IMP. The results contribute to a deeper insight on the possible impacts of precipitation extremes and support the development of appropriate adaptation and mitigation strategies to cope with climate extremes. This paper further proposes science-based policies for grassland protection, agriculture, and animal husbandry on the national or regional and herdsman scales
Keywords: Agriculture and animal husbandry; Causal factors; Inner Mongolian Plateau (IMP); Policy; Precipitation extremes